ON OBSERVATION OF ULF ELECTROMAGNETIC SIGNALS FROM REMOTE EARTHQUAKES AND DISTRIBUTION OF THEIR SOURCES ON THE EARTH’S SURFACE - B. V. Dovbnya (Геодинамика и тектонофизика)
During long-term observations, the Borok and College Geophysical Observatories have registered ultralow-frequency (ULF) electromagnetic signals from remote earthquakes. We have analysed the characteristics of such signals that occur several minutes before a seismic event. Our analysis shows that the dynamic spectra of the signals from earthquakes that occurred in different regions are similar, although the earthquakes differ in magnitude and focal depth. We investigate and discuss daily and seasonal probabilities for the occurrence of ULF electromagnetic pulses. Attention is given to the uneven distribution of their sources (i.e. earthquakes) on the earth’s surface. Our study shows that the ULF electromagnetic signals are clustered in separate zones and cells. When mapped, these clusters mark seismic electromagnetically active regions. In the northern hemisphere, a maximum cluster is found at latitudes 30–45°. In the longitudinal direction, two maximum clusters are located in the western sector. They are considered as the major and additional peaks (latitudes 120–150° and 0–30°, respectively). Examples are given to illustrate earthquake precursors in various regions. Based on the analysis results, we conclude that the occurrence of ULF electromagnetic pulses before earthquakes is universal. These pulses need to be investigated in a more detail to clarify if an upcoming earthquake is detectable from such signals a few minutes before its occurrence, and whether it is possible, in principle, to use this information for safety alerts before seismic shaking arrives.